Blast response and multi-objective optimization of graded re-entrant circular auxetic cored sandwich panels. (1st February 2023) - Jiang, Feng; Yang, Shu; Qi, Chang; Liu, Hai-Tao; Remennikov, Alex; Pei, Lian-Zheng
Highlights: Sandwich protection system against blast loads containing graded re-entrant circular (REC) auxetic core. Compared with re-entrant (RE) core with same mass, REC core can reduce MaxD by 2.2% and increase EA by 5.7%. Effects of geometric parameters and gradient parameters on blast-resistance of REC cored protection system. After multi-objective optimization, MaxD of graded core sandwich panel is reduced by 33.0%. Abstract: Explosion threat has a devastating impact on buildings, warships, vehicles and human lives, which puts forward urgent requirements for the development of explosion protection systems. In this study, a sandwich protection system against close-range blast loads containing graded re-entrant circular (REC) auxetic core was proposed, and its blast-resistance performance was investigated based on the numerical methods validated by the field blast test results in the literature. Numerical results showed that compared with the conventional re-entrant (RE) core with the same mass, the REC core can reduce the maximum displacement ( MaxD ) of the back panel by 2.2% and increase the energy absorption (EA) of the system by 5.7%. If the two cores share the same cell wall thickness, the REC core can reduce MaxD by 28.0% and increase EA by 2.1%. In addition, the effects of geometric parameters, thickness parameters and gradient parameters on the blast-resistance of REC cored protection system were examined. The results indicated that reducing the thickness of the cell wall, that is, reducing the core density, can effectively improve the blast-resistance performance. Finally, to further improve the performance of the proposed explosion protection system, multi-objective optimizations were carried out for the system with uniform and graded REC cores. The results showed that compared with the baseline model, the MaxD of the optimized uniform and graded core sandwich panels is reduced by 20.0% and 33.0%, while the areal specific energy absorption ( ASEA ) is increased by 21.2% and 23.1%, respectively. The present study shows that the re-entrant circular auxetic cored sandwich structure has great potential in blast protection applications.